2004
DOI: 10.1002/ajim.20082
|View full text |Cite
|
Sign up to set email alerts
|

The beryllium lymphocyte proliferation test: Relevant issues in beryllium health surveillance

Abstract: The Be-LPT is efficacious in medical surveillance of beryllium-exposed individuals. The PPV of the Be-LPT is comparable to other widely accepted medical tests. Confirmation of an abnormal result is recommended to assure appropriate referral for CBD medical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 32 publications
6
86
0
1
Order By: Relevance
“…The findings of that initial study were confirmed in larger studies [3] and by different investigators [4,5]. Around 10 yrs later, an immunological test (the beryllium lymphocyte proliferation test (BeLPT)) was initially used in cross-sectional studies and later in the surveillance and screening of current and former beryllium workers [6][7][8]. Those studies demonstrated that CBD was not heading for the medical archives, but that the disease was present in much greater numbers than previously reported due to misdiagnosis of overt cases and the detection of early and asymptomatic cases through immunological testing.…”
supporting
confidence: 48%
“…The findings of that initial study were confirmed in larger studies [3] and by different investigators [4,5]. Around 10 yrs later, an immunological test (the beryllium lymphocyte proliferation test (BeLPT)) was initially used in cross-sectional studies and later in the surveillance and screening of current and former beryllium workers [6][7][8]. Those studies demonstrated that CBD was not heading for the medical archives, but that the disease was present in much greater numbers than previously reported due to misdiagnosis of overt cases and the detection of early and asymptomatic cases through immunological testing.…”
supporting
confidence: 48%
“…The presence of a beryllium-specific immune response in blood is detected by the beryllium lymphocyte proliferation test (BeLPT) (11)(12)(13). This assay is used for screening and diagnosis of beryllium sensitization in the workplace and is a required component of the US Department of Energy CBD prevention program (23).…”
Section: Figurementioning
confidence: 99%
“…Beryllium sensitization is associated with the presence of circulating beryllium-specific CD4 + T cells, which proliferate in the presence of beryllium salts in culture in an MHC class II-restricted manner (6)(7)(8)(9)(10). The in vitro response forms the basis of the beryllium lymphocyte proliferation test (BeLPT), which is currently used to detect beryllium sensitization in the workplace (11)(12)(13). Progression from sensitization to CBD occurs at a rate of 6-8% per year (14) and is characterized by the accumulation of large numbers of berylliumspecific, Th1-type cytokine-secreting CD4 + T cells in the lung and granulomatous inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Stange et al reported a false positive rate of nearly 2% and a false negative rate of 32%. 35 All medical screening tests can have false positive or false negative results. A second, confirmatory abnormal BeLPT result is often required for a person to be considered sensitized to beryllium.…”
Section: Discussionmentioning
confidence: 99%